1995
DOI: 10.1146/annurev.nu.15.070195.000343
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tight-Junction Permeability During Nutrient Absorption Across the Intestinal Epithelium

Abstract: Tight junctions are located at the luminal aspect of adjacent epithelial cells and form a barrier that limits the paracellular diffusion of hydrophilic solutes. In recent years, evidence has accumulated to indicate that tight-junction permeability is regulated by the absorption of various nutrients. In this review, we present the physiological basis and importance of tight-junction regulation in intestinal epithelium. The molecular structure of tight junctions and their interactions with the cell cytoskeleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 52 publications
3
102
0
Order By: Relevance
“…In this study, no C. perfringens enumeration was performed, but improved body weight and feed conversion ratio (unpublished data), reduced intestinal lesion scores and plasma endotoxin levels of birds supplemented with xylanase indicated that xylanase greatly attenuated the negative effects of C. perfringens challenge and improved the intestinal barrier function and growth performance of birds challenged with C. perfringens. TJs create a paracellular permeability barrier and act as a fence preventing macromolecular transmission (Ballard et al, 1995). This barrier is comprised of several unique proteins including occludin, junctional adhesion molecule (JAM), claudins, and zonula occludens (ZO) (Schneeberger & Lynch, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no C. perfringens enumeration was performed, but improved body weight and feed conversion ratio (unpublished data), reduced intestinal lesion scores and plasma endotoxin levels of birds supplemented with xylanase indicated that xylanase greatly attenuated the negative effects of C. perfringens challenge and improved the intestinal barrier function and growth performance of birds challenged with C. perfringens. TJs create a paracellular permeability barrier and act as a fence preventing macromolecular transmission (Ballard et al, 1995). This barrier is comprised of several unique proteins including occludin, junctional adhesion molecule (JAM), claudins, and zonula occludens (ZO) (Schneeberger & Lynch, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial cells form a continuous intact physical barrier with tight junctions (TJs) formed with each neighbouring cell. TJs are a major regulator of paracellular permeability, and their disruption results in increased permeability to luminal antigens and bacteria that promote release of pro-inflammatory cytokines (Ballard et al, 1995). The produced pro-inflammatory cytokines may induce apoptosis of intestinal epithelia, and alter the expression or cellular distribution of TJ proteins to further deteriorate mucosal barrier function (Clark & Coopersmith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the rapidly evolving understanding about the architecture and function of the tight junction is far from complete, it is clear that the tight junction is a dynamic and complex multiprotein structure, selectively permeable to certain hydrophilic molecules, ions, and nutrients (1,2).…”
mentioning
confidence: 99%
“…1 ( The extent of this transit is affected by the composition of digesta as well as intestinal health (Ballard et al, 1995). Factors impacting intestinal health include paracellular barrier function, transcellular nutrient absorption and performance of brush border enzymes (van der Klis and Jansman, 2002).…”
Section: (A)mentioning
confidence: 99%